Pengaruh Model Project Based Learning (PjBL) Berbantuan Media Audiovisual terhadap Keterampilan Menulis Teks Ulasan Karya Fiksi Siswa SMP - Wardani, Dhea; Rasyid, Yulianti (Jurnal Bahasa dan Sastra, 2025)
This study examined the improvement of Grade 8 junior high school students’ fiction review writing skills through Project-Based Learning (PjBL) supported by audiovisual media. A quantitative one-group pretest–posttest design was employed. The sample consisted of 31 students selected through purposive (typical-case) sampling. Data were collected using a performance-based writing test administered before and after the intervention and scored with an analytic rubric covering text structure, content development, and spelling/mechanics (Indonesian orthography). Descriptive statistics and a paired-samples t-test were used for data analysis. The results indicated that the mean score increased from 45.97 (pretest) to 84.01 (posttest). The paired-samples t-test confirmed that the gain was statistically significant at the 0.05 level . These findings suggest that PjBL with audiovisual media effectively enhances students’ fiction review writing performance in the studied cohort, although accuracy in mechanics remains an area for further instructional support.